Exploring the perceptions & attitudes of tertiary students’ towards islamic banking in Bangladesh - Rahman, Munira (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.